Diversity of fungal communities on Cabernet and Aglianico grapes from vineyards located in Southern Italy - Iorizzo, Massimo; Bagnoli, Diletta; Vergalito, Franca; Testa, Bruno; Tremonte, Patrizio; Succi, Mariantonietta; Pannella, Gianfranco; Letizia, Francesco; Albanese, Gianluca; Lombardi, Silvia Jane; Coppola, Raffaele (Frontiers in Microbiology, 2024)
Grape-associated microbial community is influenced by a combination of viticultural, climatic, pedological and anthropological factors, collectively known as terroir. Therefore, grapes of the same cultivar grown in different areas can be appreciated for their distinctive biogeographic characteristics. In our previous study, we showed that the phenotypic response of Aglianico and Cabernet grapevines from Molise and Sicily regions is significantly influenced by the prevailing pedoclimatic conditions, particularly soil physical properties. However, the scale at which microbial communities differ could be important in clarifying the concept of terroir, including whether it is linked to the grape variety present in a particular vineyard. To explore this further, in the research presented here, a comparative study on the fungal communities inhabiting the berry surfaces of Cabernet and Aglianico cultivars was conducted on different vineyards located in Southern Italy (Molise, Sicily and Campania regions, the first two of which had been involved in our previous study) by using high-throughput sequencing (HTS) and multivariate data analysis. The descriptive approach through relative abundance analysis showed the most abundant phyla (Ascomycota, Basidiomycota, and Chytridiomycota), families (Cladosporiaceae, Saccotheciaceae, Pleosporaceae, Saccharomycodaceae, Sporidiobolaceae, Didymellaceae, Filobasidiaceae, Bulleribasidiaceae, and Saccharomycetaceae) and genera (Cladosporium, Aureobasidium, Alternaria, Stemphylium and Filobasidium) detected on grape berries. The multivariate data analysis performed by using different packages (phyloseq, Vegan, mixOmics, microbiomeMarker and ggplot2) highlighted that the variable “vineyard location” significantly affect the fungal community, while the variable “grape variety” has no significant effect. Thus, some taxa are found to be part of specific vineyard ecosystems rather than specific grape varieties, giving additional information on the microbial contribution to wine quality, thanks to the presence of fermentative yeasts or, conversely, to the involvement in negative or detrimental roles, due to the presence of grape-deriving fungi implied in the spoilage of wine or in grapevine pathogenesis. In this connection, the main functions of core taxa fungi, whose role in the vineyard environment is still poorly understood, are also described.